2006
DOI: 10.1042/bj20051417
|View full text |Cite|
|
Sign up to set email alerts
|

Human acyl-CoA:cholesterol acyltransferase 2 gene expression in intestinal Caco-2 cells and in hepatocellular carcinoma

Abstract: Humans express two ACAT (acyl-CoA:cholesterol acyltransferase) genes, ACAT1 and ACAT2. ACAT1 is ubiquitously expressed, whereas ACAT2 is primarily expressed in intestinal mucosa and plays an important role in intestinal cholesterol absorption. To investigate the molecular mechanism(s) responsible for the tissue-specific expression of ACAT2, we identified five cis-elements within the human ACAT2 promoter, four for the intestinal-specific transcription factor CDX2 (caudal type homeobox transcription factor 2), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…Under normal conditions, based on mRNA, protein, and enzyme activity analyses, human ACAT1 is the major isoenzyme in almost all of the tissues or cells examined, and ACAT2 is most abundantly expressed in the epical epithelium of intestines (5)(6)(7)(8)(9). Relevant to our current study is the fact that ACAT1 is highly expressed in monocytes/macrophages forming the foam cells in atherosclerotic plaques, especially at the early stage of atherosclerosis development (8)(9)(10)(11).…”
mentioning
confidence: 59%
“…Under normal conditions, based on mRNA, protein, and enzyme activity analyses, human ACAT1 is the major isoenzyme in almost all of the tissues or cells examined, and ACAT2 is most abundantly expressed in the epical epithelium of intestines (5)(6)(7)(8)(9). Relevant to our current study is the fact that ACAT1 is highly expressed in monocytes/macrophages forming the foam cells in atherosclerotic plaques, especially at the early stage of atherosclerosis development (8)(9)(10)(11).…”
mentioning
confidence: 59%
“…Previous studies have shown that Hnf1 ␣ and caudal type homeobox transcription factor 2 function as activators of the human SOAT2 promoter in intestinal Caco2 cells ( 34 ). Ϫ / Ϫ mice.…”
Section: Discussionmentioning
confidence: 98%
“…Regulation of these two genes is quite diverse in their localization and expression mechanisms [2]. ACAT1 expression is regulated by transcriptional factors such as STAT1a and Sp1 [23] while ACAT2 is regulated by Cdx2 and HNF1a [24]. STAT1a induction by interferon gamma has been shown to induce ACAT1 expression in human monocytes and thus this may be a possible activation pathway for this isoform [23].…”
Section: Introductionmentioning
confidence: 99%